Inovasi Olahan Jagung Twistcorn sebagai Pengembangan Agroindustri Lokal di Lamongan - Hamidah, Emmy; Bukhori, Imam; Santi, Idum Satia; Lisanty, Nina (Kadiri University, 2025)
Corn (Zea mays) has various health benefits derived from its carotenoid content, which gives its kernels their yellow color. Approximately 22% of this content is beta-carotene, which functions to prevent blindness due to cataracts, while xanthophyll protects cells from cancer, acts as an antioxidant, and supports the immune system and heart health. This community service activity aims to increase understanding of the optimal use of corn, specifically through the production of nutritious twistcorn snacks. This training involved the community in RT.001 RW.003 Laren Village and began with an initial questionnaire, followed by the delivery of materials on making twist corn snacks, and concluded with a final questionnaire. The material was delivered through lectures and question-and-answer discussions, which were met with enthusiasm by the participants. The results of the activity demonstrated an increase in knowledge among all participating communities following the training. Jagung (Zea mays) memiliki berbagai manfaat kesehatan yang berasal dari kandungan karotenoidnya, yang memberikan warna kuning pada bijinya. Sekitar 22% dari kandungan tersebut adalah beta karoten, yang berfungsi mencegah kebutaan akibat katarak, sementara xantofil melindungi sel dari kanker, bertindak sebagai antioksidan, dan mendukung sistem kekebalan serta kesehatan jantung. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pemahaman tentang pemanfaatan jagung secara optimal, khususnya melalui pembuatan snack jagung twistcorn yang bergizi. Pelatihan ini melibatkan masyarakat di RT.001 RW.003 Desa Laren dan dimulai dengan kuisioner awal, diikuti dengan penyampaian materi mengenai pembuatan camilan jagung twistcorn, dan diakhiri dengan kuisioner akhir. Materi disampaikan melalui metode ceramah dan diskusi tanya jawab, yang disambut dengan antusiasme peserta. Hasil kegiatan menunjukkan peningkatan pengetahuan seluruh masyarakat peserta setelah pelatihan.